Highlights from day three of the EuroSciCon 2015 Sports Science Summit. - Chawla,A; McGregor,A (Future Science OA, 2015)
This EuroSciCon Sports Science Summit represented a significant gathering of leading professionals in the field of sports science. The conference was held on 13-15 January 2015 at the O2 arena, London, UK. The chairman on the third day was Mr Greg Robertson, a specialist trainee Orthopedic surgeon from Edinburgh. The conference attracted over 80 attendants from all over the world, with 32 presentations from invited speakers and peer-reviewed submissions. This meeting report provides a summary of the best abstracts from the conference.